PENGARUH PROGRAM PEMBINAAN PONDOK PESANTREN TERHADAP MOTIVASI BELAJAR MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMPIT AL-RIDWAN KARAWANG - Qiyaafatul Haq, Jamilah; Astuti Darmiyanti; Abdul Hakim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the Islamic Boarding School Development Program on students’ learning motivation in Islamic Religious Education and Character Education (PAI-BP) at SMPIT Al-Ridwan Karawang. The study employed a quantitative approach with an ex post facto causal-comparative design. The population consisted of 66 seventh- and eighth-grade students of SMPIT Al-Ridwan Karawang. Since the population was relatively small, a total sampling technique was applied, involving all students as research participants. Data were collected through questionnaires that had been tested for validity and reliability. The data were analyzed using descriptive statistics, normality tests, linearity tests, and simple linear regression with the assistance of SPSS version 25. The results revealed that the Islamic Boarding School Development Program was categorized as moderate (71%), while students’ learning motivation in PAI-BP was also categorized as moderate (69%). The simple linear regression analysis showed a significance value of 0.000 (p < 0.05), indicating that the Islamic Boarding School Development Program had a positive and significant effect on students’ learning motivation. The regression coefficient value of 0.472 indicated a positive relationship, meaning that better implementation of the program was associated with higher learning motivation. Furthermore, the coefficient of determination (R²) was 0.302, indicating that the program contributed 30.2% to students’ learning motivation, while the remaining 69.8% was influenced by other factors outside the scope of this study. In conclusion, the Islamic Boarding School Development Program has a positive and significant effect on students’ learning motivation in Islamic Religious Education and Character Education at SMPIT Al-Ridwan Karawang.